Sessualità e diritti civili - Fagioli, Massimo (Il sogno della farfalla, 2008)
The two texts by Massimo Fagioli proposed here – an interview given to “Radio Radicale” radio station and a talk presented at a convention on “Civil love” – develop and clarify the research into human sexuality and how it relates to one’s mental reality and human identity.